2017
DOI: 10.1016/j.radonc.2017.09.041
|View full text |Cite
|
Sign up to set email alerts
|

Clustering of multi-parametric functional imaging to identify high-risk subvolumes in non-small cell lung cancer

Abstract: We designed a subregional analysis for multi-parametric imaging in NSCLC, and showed the potential of subregion classification as a biomarker for prognosis. This methodology allows for a comprehensive data-driven analysis of multi-parametric functional images.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 31 publications
(37 reference statements)
1
14
0
Order By: Relevance
“…Multiregion sequencing studies have revealed significant variations in the genetic makeup and molecular pathways across different regions in the same tumor (31). Image-based partitioning could be used to identify aggressive subregions that are important for determining prognosis and treatment response (32)(33)(34). Gillies et al used a threshold-based method to segment intratumoral regions (i.e., habitats) with prognostic value in glioblastoma (35).…”
Section: Discussionmentioning
confidence: 99%
“…Multiregion sequencing studies have revealed significant variations in the genetic makeup and molecular pathways across different regions in the same tumor (31). Image-based partitioning could be used to identify aggressive subregions that are important for determining prognosis and treatment response (32)(33)(34). Gillies et al used a threshold-based method to segment intratumoral regions (i.e., habitats) with prognostic value in glioblastoma (35).…”
Section: Discussionmentioning
confidence: 99%
“…A strong association with HIF-2α overexpression and poor clinical outcomes such as OS (HR = 1.69, 95%CI: 1.39–2.06), DFS (HR = 1.87, 95%CI: 1.2–2.92), RPS (HR = 2.67, 95%CI: 1.32–5.38), and PFS (HR = 2.18, 95%CI: 1.25–3.78), including in NSCLC were reported. Finally, non-invasive methods were also investigated such as PET, using hypoxic-dedicated tracers [ 18 F]-FAZA in a cohort of localised NSCLC [ 229 , 230 ]. Tumours with hypoxic radiological features were associated with poorer PFS and OS [ 173 , 230 , 231 ].…”
Section: Prognostic Implications Of Hypoxia In Lung Cancermentioning
confidence: 99%
“…Using a datadriven partitioning approach with PET and DWI, intratumor subregions with high SUVs and low apparent diffusion coefficients reflect high aggressiveness of a tumor and are significant predictors of survival in lung adenocarcinoma (35). Another study divided the subregions using imaging of metabolic activity (FDG-PET/CT), hypoxia (HX4 PET/CT), and tumor vasculature (DCE-CT) in NSCLC patients treated with definitive chemoradiation (36). According to that study, metabolically active subregions that were highly hypoxic and demonstrated intermediate tumor perfusion were related to high-risk tumor type and worse survival, and data-driven sub-regional analysis for multimodal imaging may be used as a biomarker to predict the prognosis of the NSCLC patients (36).…”
Section: Imaging Genomicsmentioning
confidence: 99%
“…Another study divided the subregions using imaging of metabolic activity (FDG-PET/CT), hypoxia (HX4 PET/CT), and tumor vasculature (DCE-CT) in NSCLC patients treated with definitive chemoradiation (36). According to that study, metabolically active subregions that were highly hypoxic and demonstrated intermediate tumor perfusion were related to high-risk tumor type and worse survival, and data-driven sub-regional analysis for multimodal imaging may be used as a biomarker to predict the prognosis of the NSCLC patients (36). Thus, although significant work remains to be done, the role of the radiologist is expanding to the combined application of medical images obtained from multiple modalities, leading to an informed decision for better diagnosis, staging, and treatment response.…”
Section: Imaging Genomicsmentioning
confidence: 99%